Aptech limited : hedging uncertainty and achieving service excellence - Datta, Soumyajyoti; Kapoor, Rohit (London : Neilson Journals Publishing, 2018)
Aptech Limited specialized in providing training services focussing on young professionals so that they could improve their employment potential in their industry of choice. The company implemented a "candidate-centric approach" that called for redesigning their operations into distinct training service lines for five industries. The company had to deliberate on the pros and cons of allocating corporate trainers to specialize in well-defined functional processes pertaining to specific service lines. The case emphasises the trade-off faced in service operations between service quality and workforce utilization in the midst of demand uncertainty, and juxtaposes the need for and estimation of the desired workforce to achieve the given goals of service quality and resource utilization in a competitive and less price-sensitive service industry in an emerging nation.
Orginally Published In Datta, S. & Kapoor, R. (2018). Aptech Limited: Hedging Uncertainty and Achieving Service Excellence. Operations Management Education Review, 12(1), 45-62. OMER12-0CS2.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Vocational training centers -- India